2008
DOI: 10.4049/jimmunol.181.7.5098
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic Acid Induces HO-1 Expression via the TLR2/MyD88/c-Src/NADPH Oxidase Pathway and Nrf2 in Human Tracheal Smooth Muscle Cells

Abstract: Heme oxygenase‐1 (HO‐1) is a stress‐inducible rate‐limiting enzyme in heme degradation, which confers cytoprotection against oxidative injury and provides a vital function in maintaining tissue homeostasis. Increasing reports have indicated that lipoteichoic acid (LTA) exerts as LPS as an immune system‐stimulating agent and plays a role in the pathogenesis of severe inflammatory responses induced by Gram‐positive bacteria infection. Here, we report that LTA is an inducer of HO‐1 and examine the signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 46 publications
(66 reference statements)
16
153
0
Order By: Relevance
“…of NADPH oxidase ( 31,32 ). Together, these results suggest that the responsiveness of cells to TLR4 agonists depends in part on ROS tone of cells in culture.…”
Section: Production Of Ros Is Increased In Cells Cultured In a Serum-mentioning
confidence: 53%
“…of NADPH oxidase ( 31,32 ). Together, these results suggest that the responsiveness of cells to TLR4 agonists depends in part on ROS tone of cells in culture.…”
Section: Production Of Ros Is Increased In Cells Cultured In a Serum-mentioning
confidence: 53%
“…Total RNA was isolated using TRIzol according to the protocol of the manufacturer. The cDNA obtained from 0.5 g total RNA was used as a template for PCR amplification, as previously described (11). The primers used were as follows: ICAM-1:…”
Section: Methodsmentioning
confidence: 99%
“…Previous study also showed that lipoteichoic acid (LTA) induced the formation of a TLR2/MyD88/ TRAF6/c-Src complex in human airway smooth muscle cells (11). Thus we further investigated the physical association of TLR4, MyD88, TRAF6, and c-Src in LPS-induced ICAM-1 expression by immunoprecipitation using anti-c-Src and anti-TRAF6 antibodies subjected to Western blot.…”
Section: Lps Induces Icam-1 Expression Via C-srcmentioning
confidence: 99%
See 2 more Smart Citations